Impaired Healing of a Cutaneous Wound in an Inducible Nitric Oxide Synthase-Knockout Mouse - Takashi Kitano; Hiroshi Yamada; Maki Kida; Yuka Okada; Shizuya Saika; Munehito Yoshida (Hindawi Limited, 2017)
Background. We investigated the effects of loss of inducible nitric oxide synthase (iNOS) on the healing process of cutaneous excisional injury by using iNOS-null (KO) mice. Population of granulation tissue-related cell types, that is, myofibroblasts and macrophages, growth factor expression, and reepithelialization were evaluated. Methods. KO and wild type (WT) mice of C57BL/6 background were used. Under general anesthesia two round full-thickness excision wounds of 5.0 mm in diameter were produced in dorsal skin. After specific intervals of healing, macroscopic observation, histology, immunohistochemistry, and real-time reverse transcription-polymerase chain reaction (RT-PCR) were employed to evaluate the healing process. Results. The loss of iNOS retards granulation tissue formation and reepithelialization in excision wound model in mice. Detailed analyses showed that myofibroblast appearance, macrophage infiltration, and mRNA expression of transforming growth factor b and of collagen 1α2 were all suppressed by lacking iNOS. Conclusions. iNOS is required in the process of cutaneous wound healing. Lacking iNOS retards macrophage invasion and its expression of fibrogenic components that might further impair fibrogenic behaviors of fibroblasts.